1996
DOI: 10.1175/1520-0477(1996)077<1233:angwvd>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

A New Global Water Vapor Dataset

Abstract: A comprehensive and accurate global water vapor dataset is critical to the adequate understanding of water vapor's role in the earth's climate system. To begin to satisfy this need, the authors have produced a blended dataset made up of global, 5-yr (1988-92), l°x 1° spatial resolution, atmospheric water vapor (WV) and liquid water path products. These new products consist of both the daily total column-integrated composites and a multilayered WV product at three layers (1000-700, 700-500, 500-300 mb). The ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
190
0
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 317 publications
(202 citation statements)
references
References 21 publications
(31 reference statements)
8
190
0
4
Order By: Relevance
“…An evaluation of the precipitable water field is given by Bromwich et al (2000). In comparison with the European Centre for Medium-range Weather Forecasts (ECMWF) reanalysis and the National Aeronautics and Space Administration Water Vapor Product (NVAP; Randel et al, 1996), mean values for the north polar cap were found to be comparable. However, significant spatial discrepancies were noted, particularly over lower latitude land surfaces.…”
Section: Computations and Approachmentioning
confidence: 99%
“…An evaluation of the precipitable water field is given by Bromwich et al (2000). In comparison with the European Centre for Medium-range Weather Forecasts (ECMWF) reanalysis and the National Aeronautics and Space Administration Water Vapor Product (NVAP; Randel et al, 1996), mean values for the north polar cap were found to be comparable. However, significant spatial discrepancies were noted, particularly over lower latitude land surfaces.…”
Section: Computations and Approachmentioning
confidence: 99%
“…The CPC Merged Analysis of Precipitation (CMAP) is a global monthly precipitation dataset on a 2.5 degree grid, covering the period 1979(Xie and Arkin 1997. The National Aeronautics and Space Administration Water Vapor Project global water vapor dataset (NVAP) is a water vapor and liquid water path archive at 1 degree resolution that extends from 1988-1999 (Randel et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Pemantauan ruang berbasis seperti Global Positioning System (GPS) dan penginderaan jauh dari satelit adalah satu-satunya cara yang efektif untuk menilai tingkat uap air secara global dan berbagai misi telah dilaksanakan untuk pengukuran precipitable water vapor (PWV) atau total kandungan uap air [3,[10][11].…”
Section: Pendahuluanunclassified
“…Sehingga dapat disimpulkan bahwa keadaan topografi memperngaruhi pola distribusi PWV. Hasil analisis ini sesuai dengan teori [7][8][9][10][11][12].…”
Section: Hasil Pola Distribusi Pwv Secara Spasialunclassified